Growth, inequality and politics revisited a developing country case - Balisacan, Arsenio M. (Economics Letters)
Key issues in the empirical study on growth are addressed using provincial data in the Philippines. We find a high rate of absolute convergence, a positive relationship between inequality and growth, and a positive relationship between politcal competitiveness ang growth.